Maize/soybean intercropping with nitrogen supply levels increases maize yield and nitrogen uptake by influencing the rhizosphere bacterial diversity of soil - Zhang, Liqiang; Feng, Yudi; Zhao, Zehang; Cui, Zhengguo; Baoyin, Bate; Wang, Hongyu; Li, Qiuzhu; Cui, Jinhu (Frontiers in Plant Science, 2024)
Introduction Intercropping practices play a crucial role in enhancing and maintaining the biodiversity and resiliency of agroecosystems, as well as promoting stable and high crop yields. Yet the relationships between soil nitrogen, microbes, and yield in maize cultivated under maize/soybean intercropping systems remain unclear. Methods To fill that knowledge gap, here we collected maize rhizosphere soil at the staminate stage after 6 consecutive years of maize/soybean intercropping, to investigate how intercropping and nitrogen application rates affected nitrogen utilization by crops and soil microbial community composition and function. We also examined correlations of those responses with yields, to clarify the main ways that yield is enhanced via intercropping and by nitrogenous fertilizer gradient changes generated by different nitrogen application rates. Results The amount of applied fertilizer was 240 kg N ha-1 was best for obtaining a high maize yield and also led to the greatest nitrogen-use efficiency and bacterial diversity. Under the same N application rate, intercropping increased the maize yield by 31.17% and soil nitrogen (total, ammonium and nitrate nitrogen) by 14.53%, on average, in comparison to monocropping. The enrichment of Gemmatimonas and Bradyrhizobium significantly increased the soil nitrogen content, and a greater relative abundance of Sphingomonas and Gemmatimonas increased the maize yield, whereas enrichment of Candidatus_Udaeobacter and Bradyrhizobium decreased it. The benefits of intercropping mainly arise from augmenting the abundance of beneficial microorganisms and enhancing the efficiency of N use by crop plants. Discussion This study’s findings are of key importance to bolster the stability of agro-ecosystems, to guide the scientific rational use of nitrogen fertilizers, and to provide a sound theoretical basis for achieving the optimal management of intensive crop-planting patterns and green sustainable development.